1991
DOI: 10.1007/bf00678725
|View full text |Cite
|
Sign up to set email alerts
|

Neurons with histaminelike immunoreactivity in the segmental and stomatogastric nervous systems of the crayfishPacifastacus leniusculus and the lobsterHomarus americanus

Abstract: We used a polyclonal antiserum against histamine to map histaminelike immunoreactivity (HLI) in whole mounts of the segmental ganglia and stomatogastric ganglion of crayfish and lobster. Carbodiimide fixation permitted both HRP-conjugated and FITC-conjugated secondary antibodies to be used effectively to visualize HLI in these whole mounts. Two interneurons that send axons through the inferior ventricular nerve (ivn) and the stomatogastric nerve to the stomatogastric ganglion had strong HLI, both in crayfish a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 22 publications
2
48
0
Order By: Relevance
“…Additionally, our data indicate that activity of the modulatory PS neurons in the American lobster, H. americanus, modulates the oesophageal rhythm in the CoGs by differentially utilizing histamine (Mulloney and Hall, 1991), but not Crust-MS, the PS neuron cotransmitter we identified in the present study through RT-PCR analysis. Our results, coupled with the documentation of PS neuron synaptic connectivity in the CoGs (Cazalets et al, 1990b;Meyrand et al, 1994), suggest that this modulation occurs directly within the CoGs.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Additionally, our data indicate that activity of the modulatory PS neurons in the American lobster, H. americanus, modulates the oesophageal rhythm in the CoGs by differentially utilizing histamine (Mulloney and Hall, 1991), but not Crust-MS, the PS neuron cotransmitter we identified in the present study through RT-PCR analysis. Our results, coupled with the documentation of PS neuron synaptic connectivity in the CoGs (Cazalets et al, 1990b;Meyrand et al, 1994), suggest that this modulation occurs directly within the CoGs.…”
Section: Discussionsupporting
confidence: 56%
“…Thus, for the rest of this paper, Crust-MS effects refer to the effects of short-term bath application of Crust-MS. The PS neurons contain Crust-MS, but histamine is also present, as shown previously (Mulloney and Hall, 1991;Le Feuvre et al, 2001). We therefore examined the effects of a 3ms focal application of histamine to the STG and compared it with the modulation produced by Crust-MS application.…”
Section: Ps Stimulation Crust-ms Application and Focal Histamine Appmentioning
confidence: 80%
See 1 more Smart Citation
“…Weimann et al (1993) demonstrated that the major native FMRFamide-like molecules in C. borealis are extended FLRFamide peptides (SDRN FLRFamide and TN RN FLRFamide). To detect histamine-like immunoreactivity, a rabbit polyclonal antibody generated against histamine (Accurate Chemicals) (Mulloney and Hall, 1991) was used. This antibody required the use of an EDAC fixative (see above) and was used at 1:500 (Christie, 1995).…”
Section: Abstract: Stomatogastric Nervous System; Crustacea; Projectmentioning
confidence: 99%
“…Therefore we focused our attention on the three groups of projection neurons (GPR, GN1/2, PS) that have been shown to express FLRFamide immunoreactivity. Moreover, these neurons also express cotransmitters in the adult, such as serotonin for the GPR cells and GABA for GN1/2 neurons (Cournil et al, 1990;Meyrand et al, 2000), and in other species PS neuron homologs display histamine immunoreactivity (Mulloney and Hall, 1991). Previous indirect studies suggest that, for example, the GPR neurons gradually acquire their neurotransmitter (FLRFamide, allatostatin, and serotonin) phenotype during development .…”
Section: Comparison Of Neurotransmitter Phenotype Of Embryonic and Admentioning
confidence: 99%